High-performance solid-state asymmetric supercapacitor based on Co3V2O8/carbon nanotube nanocomposite and gel polymer electrolyte. (June 2022) - Fahimi, Zohre; Moradlou, Omran
Abstract: Binary metal oxides have promise in several fields due to their tunable structure properties and high stabilities. Moreover, gel polymer electrolytes allow the fabrication of solid-state supercapacitors. In this work, to get higher specific capacitances in solid-state supercapacitors, Co3 V2 O8 /carbon nanotube (Co3 V2 O8 /CNT) nanocomposite with porous structure is proposed as the positive electrode material with appropriate morphological feature. The improved charge transfer rate at the electrode surface and quick ion diffusion due to the interconnected mesoporous channels of Co3 V2 O8 /CNT nanocomposite result in extraordinary specific capacitance of 1959.92 F g −1 at the current density of 1 A g −1 . The performance of the proposed electrode is investigated in various electrolytes including aqueous, organic, and gel polymer electrolytes. Finally, a hybrid asymmetric solid-state device is constructed with Co3 V2 O8 /CNT as positive electrode, activated carbon (AC) as negative electrode, and polyvinyl alcohol/H2 SO4 (PVA/H2 SO4 ) as gel polymer electrolyte. The specific capacitance for the device is 120.17 F g −1 at a current density of 1 A g −1 and the energy density of 37.55 Wh kg −1, which is higher than the capacitance for the KOH and organic electrolyte-based devices. The solid-state device with gel polymer maintains excellent cycling stability with retention of 95.26% after 3000 cycles. Graphical abstract: Unlabelled Image Highlights: Porous Co3 V2 O8 nanospheres was proposed as the positive electrode material with appropriate morphological feature. Low cost, environmentally friendly, and non-toxic materials were used to prepare the supercapacitor device. Co3 V2 O8 /CNT electrode exhibits enhanced specific capacitance of 1959.92 F g -1 at the applied current density of 1 A g -1 . The interconnected mesopore channels in nanospheres results the improved charge transfer rate and quick ion diffusion.